Pelatihan Penyusunan Laporan Keuangan Bagi Pelaku UMKM Di Kelurahan Gandoang - Destiana Utarindasari; Ayu Purnama; Alvia Prihatini (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
Writing financial statement is an issues which must gain some attention nowadays, this must be a point for MSME for utilizing all the facilities in order to increase their working capital. One of the facility to increase the working capital is to apply for bank credit but a minimum knowledge about financial statement is one of the obstacle to MSME, the purpose of this study is to facilitate the training for preparing financial statement for MSME in Cileungsi Gandoang District, Bogor, the author hopes that the training which has been carried out are able to help MSME to record their financial statement in order to make a decision for their activities, so that credit applications as one of the facilities to increase working capital and administrative requirements fits. With description of accounting and its elements method to conduct financial statement, the author also use Focus Group Discussion to deliver the message effectively so the MSME is able to conduct their simple financial statement for information for the shareholders, investors and other financial institutions such as bank in the future. The study showed that the MSME actors in Cileungsi Gandoang District, Bogor are able and willing to learn about the importance of preparing financial statements and hoped to expand their business to serve the local governance as their economic support